Nonspeculative Behavior and the Term Structure - Lee, Wayne Y.; Maness, Terry S.; Tuttle, Donald L. (Journal of Financial and Quantitative Analysis, 1980)
There are two well-known distinct aspects to the behavior of a risk-averse individual towards a risky proposition: the position he takes, long or short, with regard to the gamble, and the scale of the position taken–the amount by which he goes long or short. On one hand, the first aspect depends only on the individual's assessment of the expected return from the gamble relative to a safe return. The second aspect, on the other hand, will be influenced by the individual's degree of risk aversion and the level of risk of the gamble.